The fall of Baghdad - Anderson, Jon Lee 1957- (Penguin Press, 2004)
Examines the toppling of Saddam Hussein's regime, following a diverse group of Iraqis from a life of fear under Saddam's rule, through the events of the invasion and the regime's fall, to America's seizure of power and its repercussions.
Includes index.
Keywords: Hussein, Saddam <1937-2006>; Hussein, Saddam -- 1937-; Guerre en Irak, 2003-; Irakkrieg; Politik; Iraq War, 2003-; Lebensbedingungen; Golfkrieg -- 2003; Irak - Politique et gouvernement - 1991-2003; Irak - Politique et gouvernement - 2003-; Irak; Iraq -- Politics and government -- 1991-; Bagdad; Erlebnisbericht